Re-imaging the new educational professional: opportunities, challenges and consequences for Education Studies - Dave Trotman; Hilary Dunphy (Educational Futures)
The connection between Education Studies and UK Initial Teacher Training is difficult to avoid, particularly given their histories. For many working in the field this is also desirable as it offers an opportunity to reclaim cherished principles of teacher education free from the shackles of regulation and surveillance. In this paper the authors question a retrospective framing of Education Studies and, while sympathetic to the liberal-humanist traditions often embodied in these ambitions, argue instead for a reappraisal of what it means to educate through Education. Drawing on experiences of Education Studies and ITT programmes, and in conjunction with contemporary thinking around teacher professionality, the authors call for a re-imaging of the educational professional. The paper argues for Education Studies as a preparation for educational practice where moral, ethical and value conflicts are properly accounted for in evolving educational identities. The paper concludes that Education Studies has an obligation to widen the spectrum of educational practices with which it has traditionally been concerned, reaching beyond simplistic conceptions of reflection to a practice of informed educational judgement.